Aktivitas Antioksidan Polen Lebah Tetragonula testacetarsis Asal Kalimantan Timur - Bambang Mego Hantoro; Paula Mariana Kustiawan (JURNAL FARMASI DAN MAKANAN, 2024)
Bee pollen is known for its various therapeutic activities, one of which is as an antioxidant. The utilization of Tetragonula testacetarsisbee pollen from East Kalimantan is still limited, and there is little scientific information available about its antioxidant activity. This study aims to determine the compound content in Tetragonula testacetarsis bee pollen and to evaluate its antioxidant activity. The pollen was macerated using 70% ethanol to obtain a thick ethanol extract. The extract was then tested using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method with UV-Vis spectrophotometry, and the antioxidant activity was determined using the % inhibition parameter. The test results showed that the % inhibition of Tetragonula testacetarsis bee pollen was 94.77% at a concentration of 100 ppm, indicating that Tetragonula testacetarsisbee pollen has antioxidant activity.